Evaluation of clinical relevance of examining K-ras, p16 and p53 mutations along with allelic losses at 9p and 18q in EUS-guided fine needle aspiration samples of patients with chronic pancreatitis and pancreatic cancer - Salek, C; Benesova, L; Zavoral, M; Nosek, V; Kasperova, L; Ryska, M; Strnad, R; Traboulsi, E; Minarik, M (World journal of gastroenterology, 2007)
AIM: To establish an optimum combination of molecular markers resulting in best overall diagnostic sensitivity and specificity for evaluation of suspicious pancreatic mass. METHODS: Endoscopic ultrasound (EUS)-guided fine needle aspiration cytology (FNA) was performed on 101 consecutive patients (63 males, 38 females, 60 +/- 12 years; 81 with subsequently diagnosed pancreatic cancer, 20 with chronic pancreatitis) with focal pancreatic mass. Samples were evaluated on-site by an experienced cytopathologist. DNA was extracted from Giemsa stained cells selected by laser microdissection and the presence of K-ras, p53 and p16 somatic mutations was tested by cycling-gradient capillary electrophoresis (CGCE) and single-strand conformation polymorphism (SSCP) techniques. In addition, allelic losses of tumor suppressor genes p16 (INK4, CDKN2A) and DPC4 (MADH4, SMAD4) were detected by monitoring the loss of heterozygosity (LOH) at 9p and 18q, respectively. RESULTS: Sensitivity and specificity of EUS-guided FNA were 75% and 85%, positive and negative predictive value reached 100%. The remaining 26% samples were assigned as inconclusive. Testing of molecular markers revealed sensitivity and specificity of 70% and 100% for K-ras mutations (P < 0.001), 24% and 90% for p53 mutations (NS), 13% and 100% for p16 mutations (NS), 85% and 64% for allelic losses at 9p (P < 0.001) and 78% and 57% for allelic losses at 18q (P < 0.05). When tests for different molecular markers were combined, the best results were obtained with K-ras + LOH at 9p (92% and 64%, P < 0.001), K-ras + LOH at 18q (92% and 57%, P < 0.001), and K-ras + LOH 9q + LOH 18q (96% and 43%, P < 0.001). When the molecular markers were used as complements to FNA cytology to evaluate inconclusive samples only, the overall sensitivity of cancer detection was 100% in all patients enrolled in the study. CONCLUSION: EUS-guided FNA cytology combined with screening of K-ras mutations and allelic losses of tumor suppressors p16 and DPC4 represents a very sensitive approach in screening for pancreatic malignancy. Molecular markers may find its use particularly in cases where FNA cytology has been inconclusive.
Keywords: ztráta heterozygozity; Polymorphism, Single-Stranded Conformational; Sensitivity and Specificity; senzitivita a specificita; Molecular Diagnostic Techniques; Pancreatitis, Chronic; endosonografie; regulace genové exprese u nádorů; nádory slinivky břišní; Humans; lidé středního věku; diagnostické techniky molekulární; Electrophoresis, Capillary; Biomarkers, Tumor; Predictive Value of Tests; lidské chromozomy, pár 9; chronická pankreatitida; nádorový supresorový protein p53; Female; mutace; Aged; dospělí; polymorfismus konformace jednovláknové DNA; Loss of Heterozygosity; protein Smad4; senioři; lidé; Smad4 Protein; protoonkogenní proteiny p21(ras); inhibitor p16 cyklin-dependentní kinasy; elektroforéza kapilární; Endosonography; nádorové biomarkery; Adult; ženské pohlaví; Male; Pancreatic Neoplasms; Middle Aged; prediktivní hodnota testů; Proto-Oncogene Proteins p21(ras); Cyclin-Dependent Kinase Inhibitor p16; Chromosomes, Human, Pair 18; Aged, 80 and over; Chromosomes, Human, Pair 9; senioři nad 80 let; Biopsy, Fine-Needle; Mutation; lidské chromozomy, pár 18; tenkojehlová biopsie; mužské pohlaví; Gene Expression Regulation, Neoplastic; Tumor Suppressor Protein p53